1995
DOI: 10.1103/physrevlett.74.3991
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density Measurements of High Density Plasmas Using Soft X-Ray Laser Interferometry

Abstract: We have developed and used for the first time a soft x-ray interferometer to probe a large laserproduced plasma with micron spatial resolutions.A neonlike yttrium x-ray laser operating at 155 A was combined with a multilayer coated Mach-Zehnder interferometer to obtain electron density profiles in a plasma produced by laser irradiation of a CH target. The measured electron density profile has been compared to hydrodynamic simulations and shows good agreement near the ablation surface but some discrepancy exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(89 citation statements)
references
References 15 publications
0
87
0
2
Order By: Relevance
“…The density sampled by the x-ray laser occurs over a time interval dictated by the few picosecond duration of the x-ray laser pulse and its transit time through the 0.5 cm plasma column ( 16:5 ps). The electron density, n e in cm ÿ3 , is related to the measured fringe shifts as N fringe 6:68 10 ÿ20 n e L, where L is the length (cm) of the plasma being probed by the 14.7 nm x-ray laser [4]. Fringes are clearly visible less than 10 m from the target surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The density sampled by the x-ray laser occurs over a time interval dictated by the few picosecond duration of the x-ray laser pulse and its transit time through the 0.5 cm plasma column ( 16:5 ps). The electron density, n e in cm ÿ3 , is related to the measured fringe shifts as N fringe 6:68 10 ÿ20 n e L, where L is the length (cm) of the plasma being probed by the 14.7 nm x-ray laser [4]. Fringes are clearly visible less than 10 m from the target surface.…”
mentioning
confidence: 99%
“…For example, Attwood et al successfully employed a 15 ps duration, 266 nm wavelength probe to determine density profile steepening close to the target surface [1]. Also, short wavelength, , high brightness probe beams allow for characterization of large plasmas at high density with less deleterious effects from free-free absorption f/ 3 1ÿ exp ÿhc= kT g and refraction (/ 2 ) [4]. Da Silva et al first demonstrated the technique in the extreme ultraviolet with the NOVA generated a 15.5 nm Ne-like Y collisional x-ray laser, using a Mach-Zehnder interferometer with thin multilayer beam splitters [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The elongated gold-coated mirrors redirect the beam towards the second grating where they are recombined and the interference pattern is generated. Advantages of the DGI scheme over other amplitude-division soft X-ray interferometers based on thin-film beam splitters [10,14] include a higher throughput (B6% percent per arm) and a significantly increased resistance of the beam splitters to plasma debris. A Si/Sc multilayers optics system was used to image the plasma onto a CCD/MCP detector setup with 51.2 Â magnification.…”
Section: Soft X-ray Laser Interferometry Of Dense Plasmasmentioning
confidence: 99%
“…Da Silva et al conducted the first soft X-ray laser interferometry experiments using a laboratory-size 15.5 nm Nelike Y laser pumped by the Nova laser in conjunction with a Mach-Zehnder interferometer based on thin-film beam splitters [10]. Capillary discharge-pumped soft X-ray lasers, with an extremely high brightness that is similar or higher than that of their laboratory-size predecessors and a much higher repetition rate, offer the opportunity to develop portable soft X-ray tools for the diagnostics of a large variety of dense plasmas.…”
Section: Soft X-ray Laser Interferometry Of Dense Plasmasmentioning
confidence: 99%